Assessing the perceptions of the community members of Barangay Dagsa-an, Buenavista, Guimaras on the potential environmental and soio-economic impact of the proposed Panay-Guimaras-Negros bridge - Ababa, Rio Pauline G (2024.)
Perceptions play a vital role in communicating necessary information regarding the social acceptability and appropriateness of projects, conservation policies, and management efforts. Research on the local community's perception help us to understand whether they perceive the social, environmental, and economic impacts of development projects as beneficial or equitable. Various contextual factors influence perceptions thus, diverse groups and individuals can see similar situations but perceive them separately. A total forty (40) household surveys were conducted using a developed and pre-tested questionnaire to examine the perception of the local community of barangay Dagsa-an toward the proposed Panay-Guimaras-Negros bridge and identify potential benefits and challenges within the community and the environment. Key informant interviews and focus group discussion were utilized to triangulate the data collected from the surveys. Results show that the respondents are generally aware of the project and perceive it to be beneficial for the community, while also identifying the social and environmental concerns that may result form the construction and implementation of the project. The impacts are categorized into environmental, socio-cultural, and institutional, and economic aspects. Positive impacts include improved transportation and connectivity, better road infrastructure, increased tourism and market expansion, and more employment opportunities. On the other hand, negative impacts include potential threat to the endangered Irrawaddy dolphin, pollution, sedimentation, habitat disruption and disturbance, environmental degradation, increased crime rates, pressure on the natural resources, and a possible decline in fish production. This study also highlights the need for greater inclusion, community participation, and stakeholder collaboration in planning and implementation to ensure that the projects addresses social and environmental issues.
Special Problem (Master of Marine Affairs) -- [Miagao, Iloilo] : University of the Philippines Visayas, November 2024.
Keywords: Panay-Guimaras-Negros bridge -- Environmental impact; Panay-Guimaras-Negros Bridge -- Socio-ecomic impact